2013
DOI: 10.1016/j.molcel.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin-Dependent Kinases Are Regulators and Effectors of Oscillations Driven by a Transcription Factor Network

Abstract: In our mathematical model of a transcription factor network, we inadvertently reported the wrong logic rules for the TF, YHP1 in Figure 3A. In each column (A-D), the logic should read, ''MCM1 n SBF n HCM1 ^: ASH1'' (instead of ''n : ASH1''). Note also that activation edges from MCM and HCM1 to YHP1 were unintentionally omitted from the network graphs depicted in Figures 2J and S2A. Finally, in Figure 3C, the distributions for the attractors using activation logic ''D'' should be 35.94%, 64.06%, and 0.00%, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(61 citation statements)
references
References 0 publications
5
56
0
Order By: Relevance
“…In addition, the program of transcription repeated in a second cycle, despite the fact that the cells were arrested at the G1/S border by all conventional cell cycle measures. In a later study, similar results were observed in cdc28-4 cells at restrictive temperature, although the number and amplitude of the periodic genes was substantially reduced (Simmons Kovacs et al 2012).…”
Section: Cdk's Role In Cell-cycle-regulated Transcriptional Programsupporting
confidence: 72%
See 4 more Smart Citations
“…In addition, the program of transcription repeated in a second cycle, despite the fact that the cells were arrested at the G1/S border by all conventional cell cycle measures. In a later study, similar results were observed in cdc28-4 cells at restrictive temperature, although the number and amplitude of the periodic genes was substantially reduced (Simmons Kovacs et al 2012).…”
Section: Cdk's Role In Cell-cycle-regulated Transcriptional Programsupporting
confidence: 72%
“…Although these factors do not play a direct role in limiting G1/S transcription via feedback, Hcm1 indirectly activates Clb2, the feedback repressor of SBF genes, via its role in the expression of Fkh2 and Ndd1 activators of the G2/M gene cluster (Figure 1). Despite the central role of Hcm1 in the regulation of genes involved in cell-cycleregulated transcription, hcm1 mutants are viable and retain detectable periodicity of S phase gene expression (Pramila et al 2006;Simmons Kovacs et al 2012). This suggests the involvement of additional, as yet unknown, transcription factors in the regulation of this gene family.…”
Section: The S Phase Gene Clustermentioning
confidence: 99%
See 3 more Smart Citations